PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN SERUM PALSU OLEH KEPOLISIAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Ipung Syahrir Situmorang; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Health is the most important thing the human body needs. Efforts to improve the quality of human life in the field of health, is a vast and comprehensive effort. These efforts include improving public health both physical and non-physical. The Kalthhat Kalth System mentions that health concerns the aspect of life that scope and scope is very broad and complex. Serum is a blood plasma that has antibodies to fight against certain antigens. Generally serum administration is done for treatment and not prevention. For example someone who was bitten by a poisonous snake was helped by injecting a serum anti snake serum. Giving serum like this is called passive immunity because the body does not form its own antibodies. Serum contains antibodies that can fight substances / foreign bodies or germs that enter the body. Foreign substances entering the body are said to be antigens. Antibodies that can agglomerate antigens are called precipitins, which can decompose antigen called lysine and which can offer toxins called antioxins.This type of research belongs to sociological juridical research, because in this study the authors directly conduct research on the place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at Pekanbaru Pekanbaru Resort Police and Pekanbaru Pekanbaru Food and Drug Supervisory Center, while the population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, Data collection in this study with interviews, questionnaires and literature study.From the results of the study, it can be concluded that, First, to enforce the law against the crime of fake serum circulation in the jurisdiction of Pekanbaru City Police. Second, obstacles in handling the law enforcement of fake serum circulation in the jurisdiction of Pekanbaru Town Police Force, among others; Lack of human resources, lack of facilities and pre-facilities, lack of coordination with related institutions, low awareness and public legal awareness, and the deliberate acts of perpetrators to circulate false cries. Third, Efforts to overcome such obstacles; Improve coordination with related instasi, structuring human resources, improving public services. Brief suggestions from the author is to optimize the role of investigators, make agreements with relevant agencies and improve the socialization of the law regarding the dangers of the use of fake serum.Keywords: Law Enforcement-Crime-Distribution